HOW SELFING, INBREEDING DEPRESSION, AND POLLEN LIMITATION IMPACT NUCLEAR‐CYTOPLASMIC GYNODIOECY: A MODEL. (4th June 2013) - Dornier, Antoine; Dufay, Mathilde
<x xml:space="preserve">Abstract</x> Gynodioecy, the co‐occurrence of females and hermaphrodites, is often due to conflicting interactions between cytoplasmic male sterility genes and nuclear restorers. Although gynodioecy often occurs in self‐compatible species, the effect of self‐pollination, inbreeding depression, and pollen limitation acting differently on females and hermaphrodites remains poorly known in the case of nuclear‐cytoplasmic gynodioecy (NCG). In this study, we model NCG in an infinite population and we study the effect of selfing rate, inbreeding depression, and pollen limitation on the maintenance of gynodioecy and on sex ratios at equilibrium. We found that selfing and inbreeding depression have a strong impact, which depends on whether restorer cost acts on male or female fitness. When cost affects male fitness, the strength of cost has no effect, whereas selfing and inbreeding depression only impact gynodioecy by modifying the value of the female advantage. When cost affects female fitness, selfing facilitates NCG and reduces the role of strength of the cost, even when no inbreeding depression occurs, whereas inbreeding depression globally restricts the maintenance of the polymorphism. Finally, we found that pollen limitation could additionally strongly modify the dynamic of gynodioecy. We discuss our findings in the light of empirical data available in gynodioecious species.